ESTIMATION OF IMPACT RADIUS OF THE COAL PLANT STACK EMISSION USING AERMOD MODEL - Assegaf, Alimuddin H. Assegaf; Samad, Wasir (Jurnal Ilmu Kelautan SPERMONDE, 2018)
In environmental impact assessment of coal plant, it is essential to determine the radius impact. This information can be used to determine the impacted area, which will significantly receive the pollution emitted from the stack for years. In this study, we use the American Meteorological Society - Environmental Protection Agency Regulatory Model (AERMOD) model, which is a regulated model in the USA and other countries. Five years hourly meteorological data for feeding AERMET model was obtained from MM5 re-analysis data. Terrain data was extracted from the SRTM30 satellite image and converted into DEM. The parameter to be considered in this study is Sulfur Dioxide (SO2), Nitrogen Dioxide (NO2), and Total Suspended Particle (TSP). The calculation shows that the pollutions tend to disperse in the south direction by the wind direction. NO2 is more disperse than SO2 and TSP.  Calculation of impact radius indicates that concentration of all pollutants in annual average is below the national standard. For the case of the highest one hour average gives the radius impact of 18 km for NO2 and 9 km for SO2.  For the case of the highest 24 hours, only NO2 gives value beyond the standard with an impact radius of 4.5 km.  Calculation of TSP indicates that concentration is below the standard in all cases. The maximum concentration of all pollutants is detected 3 km south of the stack.